World Environmental and Water Resource Congress 2020 Water, Wastewater, and Stormwater and Water Desalination and Reuse - Ahmad, Sajjad (Civil engineer); Murray, Regan (American Society of Civil Engineers, 2020)
Selected papers from the World Environmental and Water Resources Congress 2020, held in Henderson, Nevada, May 17-21, 2020. Sponsored by the Environmental and Water Resources Institute of ASCE.This collection contains29 peer-reviewed papers on wastewater, stormwater, and water desalination and reuse.Topics include: modeling and analysis of desalination processes; stormwater management and flood control; low impact development and runoff; and wastewater treatment.This proceedings will be of interest to practitioners and researchers in all areas of water and environmental engineering.
Keywords: Water resources development -- Congresses.; elektronické knihy; electronic books